أنشر ما يلي


 

(x+7) =  x+  2. 7x   +  72

= x2 + 14 x  +  49    

(9 - y )= 9- 2.9y  + y2    

= 81 - 18y + y2       

(z -6)(z+6) = z-  62                 

= z2 -  36              

 

 

( - x + 2)( - x ) 2 + 2.(- x ) . 2  +  22

= ( -  x )+ 4(-x) + 4                    

= x2   4x  +  4                    

 

( - x - 2)( - x ) 2 - 2.(- x ) . 2  +  22   

= ( -  x )- 4(-x) + 4                       

= x2  +   4x  +  4                   

     ( - x + 2 )( x - 2 ) =  ( -   x ) - 22                        

 = x -   4                             

 

 

 

 -( x + 2)= - (x + 2 ) )                   

= - (    x +  4x  + 4   )               

=   - x2   4x  -  4                
 

 

 -( x - 2)= - (x - 2 ) )                   

= - (    x -  4x  + 4   )               

=   - x2   4x  -  4              

 

 

 

 -( x + 2)(x-2)  = - (x + 2 ) (x-2)  )                   

= - (    x -    4   )                                     

=   - x2   +    4                           

 

Welcome To My Website
hassan.ab.ma © 2017.Free Web Site